ROLE OF TAXES IN IMPORT OPERATIONS - KH.M. Kulimova (Western European Studies, 2023)
This article presents the role of taxes in import operations, the amount of indirect taxes in state budget revenues, the amount of customs duty in state budget revenues, the composition of activities related to the increase in customs duty, the procedure for taxation when importing goods into the country, stages of control of movement of imported goods and prevention of violations of taxes and customs fees, import dynamics of the Republic of Uzbekistan with major partner countries were studied. Also, scientific discussions and proposals were made to study the role of taxes in import operations.
Keywords: export; import; customs